Paesaggi dell’interstizio. Per un Illuminismo post-coloniale (Itinera, 2024)
The landscape of tomorrow can be imagined today starting from events currently emerging from what Michel Foucault called “the interstice”. According to him, the interstice is the gray area that lies between the fundamental choices and exclusion’s strategies that every culture accomplishes to affirm its identity. Some of these interstices have been brought to light precisely in the context of landscape theories, notably by Gilles Clément. Others, however, are now emerging in political fields where landscape is not the object of a theory, but a reference for struggle and contestation. Thus, starting from a visit to the 2024 Venice Art Biennale, this essay outlines the intertwining between some interstitial movements of today - post-colonial studies, migrations, queer identities - and their impact on a possible landscape to come: not identitarian but fluid, inclusive and open towards a new idea of cosmopolitism.
Keywords: Landscape; Marginalities; Post-colonial studies; Cosmopolitism